EKSISTENSI WAKAF TUNAI DALAM TINJAUAN MASLAHAH MURSALAH - Jafar, Wahyu Abdul (Alhurriyah, 2019)
AbstractCash waqf exists because of the demands of modern times that all things are easy, practical and simple. However, behind all the convenience provided by cash waqf still leaves a fundamental problem, namely the issue of the legal status of cash waqf. In this study, the researcher explained in detail the issue of the legal status of cash waqf from the perspective of maslahah mursalah. This study included the literature research category, and analyzing the data obtained, researchers used a prescriptive analysis approach. The data collection technique used is documentation technique. After an in-depth study obtained a conclusion that the terms of the term in the cash waqf have been considered legitimate, because the conditions are still good (Maslahah that is really realized in real field), maslahah ammah (Maslahah that is general is not only enjoyed by a certain group of people) , maslahah mulaiman bi syar'i (Maslahah which is in harmony and not contrary to the Shari'ah) has been fulfilled in cash waqf. So that the legal status of cash waqf is halal. Moreover, the requirements of al habsu ma'a baqo aynihi (holding items without removing the essence) also remain in cash waqf.Keywords: Existence, Maslahah Mursalah, Cash Waqf.  AbstrakWakaf tunai lahir karena tuntutan zaman modern yang menghendaki segala sesuatu bersifat mudah, praktis dan simple. Namun, dibalik semau kemudahan yang diberikan wakaf tunai masih menyisakan persoalan mendasar, yakni persoalan legalitas hukumnya. Melalui kajian ini peneliti memaparkan secara mendetail persoalan status hukum wakaf tunai ditinjau dari perspektif maslahah mursalah. Penelitian ini termasuk kategori penelitan pustaka, sedangkan dalam menganalisi data yang diperoleh, peneliti mengunakan pendeketan analisis preskriptif.  Teknik pengumpulan data yang dipergunakan adalah teknik dokumentasi. Setelah dilakukan kajian mendalam diperoleh sebuah kesimpulan bahwa syarat berhujjah dalam wakaf tunai sudah diangap sah, karena syarat maslahah haqiqi (Maslahah yang benar benar terwujud secara real dilapangan), maslahah ammah (Maslahah yang bersifat umum bukan hanya dinikmati oleh seseorang atau kelompok orang tertentu saja), maslahah mulaiman bi syar’i (Maslahah yang selaras dan tidak bertentangan dengan syari’at) sudah terpenuhi pada wakaf tunai. Sehinga status hukum wakaf tunai adalah halal. Apalagi persyaratan al habsu ma’a baqo aynihi (menahan barang dengan tidak menghilangkan dzatnya) juga tetap ada dalam wakaf tunai.Kata kunci: Eksistensi, Maslahah Mursalah, Wakaf Tunai.